Soft Power in Practice: Cultural and Educational Micro-Diplomacy between Indonesia and the Czech Republic - Daniella Firgia Wehelmien Salmun; Joseph Viktor Kalembang; Rudi Rohi (Jurnal Ilmiah Global Education, 2026)
This research examines how cultural and educational diplomacy function as instruments of soft power in strengthening bilateral relations between Indonesia and the Czech Republic. It addresses the research gap in understanding how educational exchanges and cultural initiatives contribute to people-to-people diplomacy within less-studied bilateral contexts. Employing a qualitative descriptive approach, the study utilizes a systematic literature review as the main method of data collection, complemented by autoethnographic reflections derived from the author’s experience as an IISMA awardee in the Czech Republic. Data were obtained from official government documents, peer-reviewed academic journals, embassy publications, and institutional communications from both nations. The findings reveal that Indonesia’s cultural and educational diplomacy through programs such as IISMA, Darmasiswa, language teaching, and joint cultural festivals has effectively enhanced mutual understanding and fostered Indonesia’s positive image abroad. These initiatives serve as soft power mechanisms that attract foreign publics through shared learning and cultural appreciation, creating sustained engagement beyond state-level diplomacy. Despite these achievements, Indonesia’s approach remains fragmented due to the absence of a cohesive national branding strategy and limited inter-agency coordination. Strengthening collaboration among ministries, universities, and cultural institutions is essential to maximizing the impact of soft power. The study concludes that integrating educational and cultural diplomacy under a unified framework can significantly advance Indonesia’s strategic influence and bilateral partnership with the Czech Republic.